Seed spices adding aroma to the income of farmers - Singh, Balraj (Indian Horticulture, 2019)
Seed spices are ‘The Pride of our Nation’, as India is the largest producer and consumer of seed spices across the globe. Annually, only 10% of the seed spices produced are exported which meet the 50% of the world’s demand. Among seed spices, cumin and coriander are major crops, contributing nearly 80% to the annual seed spice production followed by fennel and fenugreek. Depending upon area under cultivation, other minor seed spices are ajwain, dill, nigella, celery, anise and caraway. Few of the minor seed spices are getting momentum in production and export and may be in high demand in coming times specifically ajwain, celery and dill. These are known for their aroma, flavour and medicinal values. They add more taste and help in maintaining human health. The production status of India has been well enough to meet the annual demand. This self-sufficiency has never pressurized to intensify the research on these crops. But now with the accelerating population load and high opportunity to sell the produce in any corner of the world, the need has arisen to develop the technologies to harvest more from per unit area and through value-addition for doubling the farmer’s income.